1983
DOI: 10.1063/1.332389
|View full text |Cite
|
Sign up to set email alerts
|

The nature of defect layer formation for arsenic ion implantation

Abstract: A series of {100} silicon wafers were implanted with As ions over the range of 1×1013 at. cm−2 to 1×1016 at. cm−2 with energies of 50, 100, and 190 keV, using a commercial ion implanter, the Varian 200-DF4. Two end stations were used, the Waycool which provided good contact between the wafers and a thermal sink and the Wayflow, which holds the wafers without any provision for obtaining such contact. Precise values of amorphous layer depth were obtained by a newly developed technique, using direct measurement o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

1986
1986
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(19 citation statements)
references
References 16 publications
1
18
0
Order By: Relevance
“…Popescu and Boca 7 have shown a correlation between the refractive index of an ion implanted sample and the degree of disorder in the lattice structure. Prussin et al 8,9 have shown that for the relatively heavy P + and As + ions implanted in Si at a high energy, there is a dose at which the subsurface amorphous layer grows sufficiently large so that the surface crystalline layer ceases to exist, and that at some higher dose dynamic annealing results in the contraction of the amorphous layer thickness and the reformation of a crystalline or polycrystalline surface layer. The lower degree of damage caused during the B + implantation process results in the disappearance of the crystalline surface layer at a dose of approximately 10 16 pared to a dose of approximately 10 14 cm −2 for As + at energies of 50, 90, and 190 keV.…”
mentioning
confidence: 98%
“…Popescu and Boca 7 have shown a correlation between the refractive index of an ion implanted sample and the degree of disorder in the lattice structure. Prussin et al 8,9 have shown that for the relatively heavy P + and As + ions implanted in Si at a high energy, there is a dose at which the subsurface amorphous layer grows sufficiently large so that the surface crystalline layer ceases to exist, and that at some higher dose dynamic annealing results in the contraction of the amorphous layer thickness and the reformation of a crystalline or polycrystalline surface layer. The lower degree of damage caused during the B + implantation process results in the disappearance of the crystalline surface layer at a dose of approximately 10 16 pared to a dose of approximately 10 14 cm −2 for As + at energies of 50, 90, and 190 keV.…”
mentioning
confidence: 98%
“…The temperature of the wafer during implant modifies the dynamic anneal, affecting the onset of amorphization and the final depth of the a-layer. The surface of the wafer tends to warm up as the implantation proceeds as a consequence of the energy transferred to the lattice by the incoming ions [12]. A good cooling system is necessary to keep the wafer temperature constant and to ensure a good temperature control during implant.…”
Section: Resultsmentioning
confidence: 99%
“…Mechanistically, the generation of a very high temperature in the envelope immediately surrounding the path of the implanted ion may explain this behavior. Specifically, Prussin et al (1983) suggested that such localized thermal spikes may be conceived as achieving a higher amorphous to crystalline transformation rate compared with that expected from the average equilibrated substrate temperature. Thus, it may be argued that the formation of an amorphous zone is indeed temperature-dependent.…”
Section: Resultsmentioning
confidence: 99%